Spinal Nerves, Injuries: Diagnosis and Treatment Methods (International Journal of Scientific Trends, 2024)
This article provides information on spinal nerve injuries, their diagnosis, and treatment methods. Spinal cord injuries are one of the pressing issues in neurology. Spinal nerves, an integral component of the peripheral nervous system, play a pivotal role in motor, sensory, and autonomic signal transmission. This article aims to elucidate the intricate anatomy, functions, and clinical implications of spinal nerve injuries, focusing on diagnostic modalities and contemporary therapeutic interventions.